MWA tied-array processing II: Polarimetric verification and analysis of two bright southern pulsars. (2019) - Xue, Mengyao; Ord, S. M.; Tremblay, S. E.; Bhat, N. D. R.; Sobey, C.; Meyers, B. W.; McSweeney, S. J.; Swainston, N. A.
Abstract: Polarimetric studies of pulsars at low radio frequencies provide important observational insights into the pulsar emission mechanism and beam models, and probe the properties of the magneto-ionic interstellar medium (ISM). Aperture arrays are the main form of next-generation low-frequency telescopes, including the Murchison Widefield Array (MWA). These require a distinctly different approach to data processing (e.g. calibration and beamforming) compared to traditional dish antennas. As the second paper of this series, we present a verification of the MWA's pulsar polarimetry capability, using two bright southern pulsars, PSRs J0742–2822 and J1752–2806. Our observations simultaneously cover multiple frequencies (76–313 MHz) and were taken at multiple zenith angles (ZA) during a single night for each pulsar. We show that the MWA can be reliably calibrated for ZA ≲45° and frequencies ≲270 MHz. We present the polarimetric profiles for PSRs J0742–2822 and J1752–2806 at frequencies lower than 300 MHz for the first time, along with an analysis of the linear polarisation degree and pulse profile evolution with frequency. For PSR J0742–2822, the measured degree of linear polarisation shows a rapid decrease at low frequencies, in contrast with the generally expected trend, which can be attributed to depolarisation effects from small-scale, turbulent, magneto-ionic ISM components. This effect has not been widely explored for pulsars in general and will be further investigated in future work.